Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1051/0004-6361/202142011
|View full text |Cite
|
Sign up to set email alerts
|

The Close AGN Reference Survey (CARS)

Abstract: Context. Active galactic nuclei (AGN) are thought to be responsible for the suppression of star formation in massive ∼1010 M⊙ galaxies. While this process is a key feature in numerical simulations of galaxy formation, it has not been unambiguously confirmed in observational studies yet. Aims. The characterization of the star formation rate (SFR) in AGN host galaxies is challenging as AGN light contaminates most SFR tracers. Furthermore, the various SFR tracers are sensitive to different timescales of star form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 209 publications
2
11
0
Order By: Relevance
“…Using a relationship between the 𝐿 2−10 keV of the CIE and star formation rate (SFR) (Franceschini et al 2003), the SFR of Mrk 1239 was found to be 4 − 6 M yr −1 . This is comparable with the SFR of < 7.5 M yr −1 measured using PAH signatures (Ruschel-Dutra et al 2016), ∼ 3.5 M yr −1 found using SED fitting (Gruppioni et al 2016), and ∼ 2.1 M yr −1 found using IR measurements (Smirnova-Pinchukova et al 2022). To fully probe the soft band of this galaxy and determine the origin of the 0.91 keV feature conclusively deeper observations of Mrk 1239 were needed.…”
Section: Introductionsupporting
confidence: 82%
“…Using a relationship between the 𝐿 2−10 keV of the CIE and star formation rate (SFR) (Franceschini et al 2003), the SFR of Mrk 1239 was found to be 4 − 6 M yr −1 . This is comparable with the SFR of < 7.5 M yr −1 measured using PAH signatures (Ruschel-Dutra et al 2016), ∼ 3.5 M yr −1 found using SED fitting (Gruppioni et al 2016), and ∼ 2.1 M yr −1 found using IR measurements (Smirnova-Pinchukova et al 2022). To fully probe the soft band of this galaxy and determine the origin of the 0.91 keV feature conclusively deeper observations of Mrk 1239 were needed.…”
Section: Introductionsupporting
confidence: 82%
“…Together with the LOS projection, different ionization conditions are inevitably captured within one spaxel. Furthermore, different ISM metallicities and densities lead to the star-forming cloud occupying a large area in the BPT diagram (e.g., Smirnova-Pinchukova et al 2022). Nonetheless, the vast majority of spaxels in the MUSE NFM FOV is consistent with excitation through SF.…”
Section: Excitation Mechanismmentioning
confidence: 99%
“…Nearby, low-luminosity AGNs mainly lie in the green valley (e.g., Salim et al 2007;Leslie et al 2016), the sparsely populated region with reduced SFR below the MS, or are altogether quiescent (Ho et al 2003). By contrast, their more luminous counterparts, the quasars, can be found below (e.g., Shimizu et al 2015;Stemo et al 2020), on (e.g., Husemann et al 2014;Woo et al 2017;Smirnova-Pinchukova et al 2022), or even above (e.g., Jarvis et al 2020;Shangguan et al 2020b;Xie et al 2021;Koutoulidis et al 2022) the starforming galaxy MS. Several factors contribute to this confusing status of affairs, including the wavelength used for sample selection (X-ray, optical, infrared, or radio), the methodology and uncertainties associated with SFR and stellar mass determination, and even the very shape and normalization of the MS used for reference comparison. Recent works suggest that the position of an AGN relative to the MS is correlated with the Eddington ratio (e.g., Shimizu et al 2015;Ellison et al 2016;Woo et al 2020;Torbaniuk et al 2021), with higher SFRs found in hosts of AGNs with higher Eddington ratio.…”
Section: Introductionmentioning
confidence: 99%